Research on the Phase Transformation of a Newly Developed Carbonitride-Strengthened Martensitic Heat Resistant Steel - Zhang, Wenfeng; Pan, Ping; Zhou, Jun; Xiong, Wei; Liu, Yunqiang; Liu, Xiaogang; Yan, Wei (Frontiers in Materials, 2022)
The phase transformation behavior of nitrides-strengthened martensitic (NSM) heat resistant steel, showing excellent creep behavior under 500°C, was studied in this article. The results showed that during the heating procedure, the formation of austenite was composed successively by intermetallic compound formation in martensite, crystal structure shift from body-centered cubic (BCC) to face-centered cubic (FCC), martensite/ferrite grain boundary migration, austenite nucleation, and growing. The crystal structure switch from BCC to FCC was sensitive to temperature, while the switch from FCC to BCC was only done with phase transformations. During the continuous cooling procedure, the carbide-free bainite would form if the cooling rate was beneath the critical cooling rate. The critical cooling rate was defined as 0.5°C/s for single martensite in NSM steel, according to its inconsistent results of microstructure and continuous cooling transformation (CCT) expansion curve under this condition. Two phase transformation zones were detected in NSM steel: one was a nose-shaped bainite zone and the other was a stripe-shaped martensite zone.